Artificial Intelligence in Indonesia’s Financial Sector: Regulatory and Islamic Law Perspectives - Sholahuddin Al-Fatih; Putri Shafarina Thahir; Nafik Muthohirin; Norhasliza Ghapa (Justicia Islamica, 2025)
The Indonesian financial sector still faces fundamental challenges in the form of low investor participation, technological limitations, cyber risks, and regulatory uncertainty that affect banking and Islamic finance. This study positions Artificial Intelligence (AI) as a transformational solution to improve efficiency, mitigate risk, and protect consumers. The method employed is prescriptive legal research on regulations, including the Electronic Information and Transactions Law, the Personal Data Protection Law, and OJK Guidelines, which are analysed within the framework of Islamic law and legal effectiveness theory. The findings indicate that the application of AI has the potential to enhance risk assessment, fraud detection, portfolio optimisation, and market forecasting when supported by a robust legal framework. This study confirms that compliance with maqāṣid al-shariah, particularly ḥifẓ al-māl, justice, and amanah, will ensure that AI is used ethically to achieve transparency and data protection. Therefore, it is necessary to formulate an AI bill, strengthen the role of the OJK, and prepare a special fatwa from Islamic authorities to ensure the responsible implementation of AI in Indonesia's financial sector.